The role of pregnancy-associated plasma protein-a level in the first trimester of pregnancy and clinical outcome in an urban referral centre - T., Lavanya; R., Premalatha; Thakkar, Nandita A.; Jawahar, Latha; Rajendran, Priya Kannappa; E., Geethanjali; Rajan, Swetha V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Estimation of serum PAPP-A levels studied predictability for adverse perinatal outcome. This case control study tries to establish the association between low PAPP-A levels among the pregnant woman and adverse maternal foetal outcome. Methods: This is an case-control study during 2017-2018 in the women delivered at Department of OBG at Mehta Hospitals. Women delivered in the labour room had a first trimester screening of PAPP-A level were explained, taken informed consent, questionnaire which include detailed antenatal history, mode of delivery and baby data. Depending upon outcome, the subjects are classified as case group or control group, out of the study sample of 264 subjects, 88 patients who had complications were taken as cases and 176 patients with no complications taken as control were undertaken. Results: Low PAPP-A level (<0.5 MoM) showed high incidence of PIH and preeclampsia, followed by IUGR and Preterm. PAPP-A level >0.5 MoM, normal outcome is more than the adverse outcome. The difference in the PAPP-A levels is statistically significant. In women with low PAPP A level, low birth weight found statistically significant when compared with <0.5 PAPP A level. The sensitivity of PAPP A levels in identifying the complicated outcomes was 17.04%.The specificity was 98.85%. The positive predictive value of predicting the complications was 88.23% and negative predictive value of 70.44%. Conclusions: The low PAPP-A levels confirmed during first trimester of pregnancy is associated with adverse maternal and foetal outcome such as PIH, preeclampsia, preterm, IUGR and LBW.